2018
DOI: 10.1111/1744-7941.12176
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate governance on firms’ decent work policies in Japan

Abstract: It is often argued that globalization of financial markets leads to change in firms’ human resource practices and employees’ well‐being. To examine the effect of corporate governance on employees’ well‐being, we examine the determinants of firm policies on decent work. Decent work was proposed as a goal by the International Labour Organization, and includes such dimensions as ‘work in conditions of freedom’, ‘equity in work’ and ‘security in work’. We develop a scoring system for firms’ policies on decent work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
4
0
3
Order By: Relevance
“…Under current UK legislation, they have an obligation to serve the 'public benefit', which is underpinned by making their residual claimants their stated beneficiaries. Although comparisons are limited, a series of studies of for-profit and non-profit nursing homes found that, consistent with the idea of prosocial motivation, the latter were more likely to delegate to their employees, and provided better quality for care dimensions that are hard to monitor (Ben-Ner et al, 2015, 2018. As the latter organizations' public purpose is fixed, their management is in effect committed to specific prosocial goals, enabling it to draw on 'donated labour' (Francois, 2003;Hansmann, 1996).…”
Section: Public Purpose and Charitable Organizationsmentioning
confidence: 99%
“…Under current UK legislation, they have an obligation to serve the 'public benefit', which is underpinned by making their residual claimants their stated beneficiaries. Although comparisons are limited, a series of studies of for-profit and non-profit nursing homes found that, consistent with the idea of prosocial motivation, the latter were more likely to delegate to their employees, and provided better quality for care dimensions that are hard to monitor (Ben-Ner et al, 2015, 2018. As the latter organizations' public purpose is fixed, their management is in effect committed to specific prosocial goals, enabling it to draw on 'donated labour' (Francois, 2003;Hansmann, 1996).…”
Section: Public Purpose and Charitable Organizationsmentioning
confidence: 99%
“…Jacoby (2007) studied the activities of foreign financial investors in Japan and also concluded that their impact on HR policies, and even corporate governance reform as a whole, has been modest at best. More recently, however, Kubo (2018) found that foreign ownership and outside director ratio significantly affect firms' decent work policies, possibly because of investors' incentive to raise profitability or enhance reputation.…”
Section: Divergence In Employment Systems In Japanmentioning
confidence: 99%
“…Várias publicações apontaram mecanismos e estratégias que promoveriam o trabalho decente, como mudanças na governança corporativa (Kubo, 2018) e enfoques humanistas de organização do trabalho (Carr, McAuliffe, & MacLachlan, 2014), mas que a falta de trabalho decente reduziria a possibilidade de um trabalho significativo (Di Fabio & Blustein, 2016).…”
Section: Análise De Conteúdo Das Potenciais Contribuições Da Psicologunclassified
“…A principal contribuição do conceito de trabalho decente para o campo da psicologia seria conseguir reunir e articular temas relativos ao trabalho que ficam dispersos em estudos específicos (Pereira et al, 2019), como, por exemplo, satisfação no trabalho (Duffy et al, 2019), bem-estar (Autin et al, 2019;Giunchi, Vonthron, & Ghislieri, 2019;Kubo, 2018) e trabalho significativo (Di Fabio & Blustein, 2016;Kenny et al, 2016;Lysova, Allan, Dik, Duffy, & Steger, 2019), buscando uma análise ampliada e mais complexa do trabalho nas mais variadas situações (Blustein et al, 2017). E os principais problemas a serem resolvidos em relação ao conceito de trabalho decente seriam que ele é um conceito mais relevante para países desenvolvidos, portanto descontextualizado para parte do mundo (Santos, 2019), ainda é pouco estudado, a maioria dos estudos analisa o conceito parcialmente, há poucos instrumentos de mensuração de componentes do trabalho decente, e há poucas populações distintas estudadas (Blustein et al, 2016;Dodd et al, 2019;Pereira et al, 2019).…”
Section: Análise De Conteúdo Das Potenciais Contribuições Da Psicologunclassified